PRE-SOWING SEED BIO-PRIMING IN OKRA: RESPONSE FOR SEED PRODUCTION - A. K. RAI,; A. K. BASU, (The Bioscan, 2014)
Seeds of eight varieties of okra: Lalu, Arka Anamika, Ramya, Satsira, Lady Luck, Debpusa Jhar, Japani Jhar and Barsha Laxmi were bio-primed with Trichoderma viride and Pseudomonas fluorescens, and sown in the field in Split-plot Design with three replications along with the unprimed control in two consecutive summer seasons of 2011 and 2012 to assess the variation in response of individual varieties for seed yield and its attributes. Trichoderma viride was improved plant length as 108.21cm and 112.25 cm for variety Arka Anamika, maximum pod length i.e. 19.01 and 19.21 as well as in pod diameter as 16.64 mm and 16.85 mm for Lalu variety in first and second year respectively. Overall seed yield per plant was as maximum as 49.14g and 51.58g in 2011 and 2012 respectively for Lalu, while it was lowest for Lady Luck (24.13g and 25.69g) in both the years. Expression for response towards individual bio-inoculants for individual varieties varied, which indicate the existence of genotypic response in enhancing the seed yield of individual varieties after pre-sowing bio-primed of seeds.From these findings it can be concluded that the bio-priming with compatible bio-agents will enhance the plant growth and yield attributes.